(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Social media is increasingly becoming a key platform in disseminating information to the masses. With its free platform and wide audience penetration, various topics are shared across which also includes promoting environmental awareness. However, just like various other topics, any digital information constantly competes for user attention and consumption. The information design strategy put in place must be understood to assess user perception towards the content where a well-designed information will motivate users to like and share content. A study employing Instagram post-type categorization and survey probing user perception was carried out in the context of NGOs championing recycling efforts. The findings show that users prefer visualized information. The results can be used as a guideline for digital information designers to improve the information design technique particularly in the context of creating awareness that could potentially dive into virality element fitting with user perception and preferences.